Integrated fertilization with organic manure and Trichoderma enhances wheat productivity and soil nutrient availability - Ren, Li; Lv, Jilong; Zhang, Fuli; Dou, Bingqian; Li, Lantao; Wang, Yilun; Zhang, Yinjie (Frontiers in Plant Science, 2025)
Reducing chemical fertilizer application combined with organic fertilizers has been demonstrated to be an effective strategy for enhancing soil fertility and increasing crop yields. However, the effects of organic fertilizer combined with Trichoderma application on wheat yields and soil nutrients remain poorly understood. Here, a field experiment was conducted in 2022, including: no nitrogen (N) application (NoN), 100% chemical fertilizer N (CN), 80% chemical fertilizer N and 20% manure N (CNM), and 80% chemical fertilizer N, 20% organic fertilizer N, and Trichoderma (CNMT) treatments. In comparison to CN, both CNM and CNMT significantly enhanced wheat yield, soil organic matter content, and soil nutrient levels, with CNMT demonstrating a more pronounced effect. CNMT significantly increased wheat yield, grain number, dry matter accumulation in grains and roots by 11.4%, 9.9%, 17.4%, and 11.9%, N accumulation in grains and roots by 24.9%, and 9.83%, and phosphorus (P) accumulation in straw, grains and roots by 13.8%, 33.5%, and 8.9%. CNMT significantly increased the contents of organic matter, hydrolyzable amino sugar N, H2O-P, NaHCO3-Pi, NaHCO3-Po, NaOH-Pi, and NaOH-Po in rhizosphere and non-rhizosphere soils. Redundancy analysis showed that organic matter was the main factor affecting the morphological distribution of N and P in both rhizosphere and non-rhizosphere soils. CNMT significantly increased the diversity of microbial communities and enhanced complexity and stability of the microbial network. Overall, the combination of chemical fertilizer, manure, and Trichoderma (80% chemical fertilizer N, 20% organic fertilizer N, and Trichoderma) can significantly increase soil organic matter, enhance the potential for N supply, reduce the fixation of P, promote the diversity of soil microbial communities, improve the uptake and utilization of nutrients by crops, and increase wheat yield.